2012
DOI: 10.1108/00400911211210215
|View full text |Cite
|
Sign up to set email alerts
|

Predicting career advancement with structural equation modelling

Abstract: Purpose -The purpose of this paper is to use the authors' prior findings concerning basic employability skills in order to determine which skills best predict career advancement potential. Design/methodology/approach -Utilizing survey responses of human resource managers, the employability skills showing the largest relationships to career advancement were used in a regression analysis. The regression results generated structural equation models. Findings -According to human resource managers, leadership skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Professors identified that interpersonal skills, followed by work ethic and leadership skills are most needed, and human resource managers identified that literacy-numeracy skills, followed by work ethic and leadership skills are most needed. In the second study, management skills, leadership skills and basic literacy-numeracy skills were found to be statistically significantly and positively correlated with perceptions of career advancement potential (Heimler et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 82%
See 1 more Smart Citation
“…Professors identified that interpersonal skills, followed by work ethic and leadership skills are most needed, and human resource managers identified that literacy-numeracy skills, followed by work ethic and leadership skills are most needed. In the second study, management skills, leadership skills and basic literacy-numeracy skills were found to be statistically significantly and positively correlated with perceptions of career advancement potential (Heimler et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 82%
“…In a comprehensive study, Rosenberg and colleagues (Rosenberg et al, 2012;Heimler et al, 2012) triangulate recently graduated students, professors and human resource managers perceptions to develop an multiple stakeholder awareness of how employability skills predict career advancement potential of undergraduate students. In the first of two studies, Rosenberg et al (2012) identified that students, professors and human resource managers have differing perceptions of the factors of employability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Contemporary evidence also suggests that though B-schools have responded to the current dynamic environment by adapting a more business-like approach to prepare students according to the industry (Pellegrino and Hilton, 2012;Rosenberg et al, 2012;Mourshed et al, 2012;Heimler et al, 2012), scanning the horizon and identifying new markets and opportunities for students' growth, some business schools remain ardently against a more business-like approach, considering it to work against academic clarity and research excellence, expected of universities (Curtis and Samy, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies noted that student leaders, especially those in big unions and organisations, have great power, authority, and public resources that might be misused (Guan and Yuan, 2019). These actions may affect one's future work ethic (Heimler et al, 2012;Phillips et al, 2017) and suggest that being in a leadership position does not always mean that the student is a good leader or is respected by peers (Komives et al, 2009;Roulin and Bangerter, 2013). Other data have shown that student leaders who consume more alcohol on average than the members of their respective organisations significantly increase their chances of drinking as students, whether in China or other countries (Li, 2013;Spratt and Turrentine, 2001).…”
Section: Discussion and Suggestionsmentioning
confidence: 99%